ANALISIS YURIDIS LEGALITAS PEMBERIAN HAK MILIK YANG DIGUNAKAN OLEH PERKEBUNAN PERSEORANGAN (STUDI DI KABUPATEN PADANG LAWAS) - RAHMAT FAUZAN DAULAY (PREMISE LAW JURNAL, 2017)
The legal ground for the transfer of a title over a piece of land to an individual or a corporation is contained in Article 4 paragraph (1) of UUPA (the Land Act); which says, “based on the State’s right of control as referred to in Article 2, several kinds of rights are determined concerning the surface of the Earth, which is called land which may be granted to and owned by an individual and by corporation”. The provision of legal certainty to the control and the exploitation in plantation with wide surface area is regulated in UUPA by granting HGU (leasehold). The Laws and regulations on managing Plantation Business have been stipulated in the Law No. 18/2004 in conjunction with the Law No. 39/2014 concerning Plantation, also the Decree of the Ministry of Agriculture No. 98/PERMENTAN/OT.140/9/2013 on the Guidelines on the Plantation Business Permit regulating that a plantation with 25 (twenty five) hectares or more of surface area shall own IUP-B (Plantation Business Permit for Cultivation) Keywords: Individual Plantation, Title, HGU (Lease-Hold)